KOMUNIKASI PADA TEATER BANGSAWAN DALAM MENYAMPAIKAN PESAN SEJARAH DAN BUDAYA MELAYU DI RIAU - Saipudin Ikhwan; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Communications also occur in a theater, because there are people who come together and work together to deliver the message through theater. Messages and symbols designed by the director to convey meaning to the audience. Theater royalty is a kind of traditional Malay arts that still exists today. This research aims to determine how the communication that occurs in the theater nobility in conveying the message of history and culture in the Riau Malay. This study uses a qualitative method. The number of informants are as many as six people. Techniques used in the determination of the subject is purposive. The data is then discussed and analyzed through interactive data analysis model. Data collection techniques are in-depth interviews, participant observation, and documentation. Mechanical checks the validity of the data using techniques extension of participation and triangulation techniques. The results showed that the process of the nobility theater is basically the process of communication. Bangsawan theater has symbols Malay ranging from theme stories, fashion, artistic Malay language until the system can be used as a medium to convey the message history and Malay culture. Symbol interpreted by players and spectators differ depending knowledge of the history and culture of the Malays. An environment that is very supportive of the nobility theater is a show that happens in the building staging. People who are involved in the theater is not only the aristocratic background of Malay culture. but there are also people outside of descent and Malay culture. The process of the theater nobility are: 1) The process of selecting text, 2) process of exercise and, 3) The performance theater. Keyword: ProcessCommunication, Theatre Bangsawan, Message History and Malay